(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Cervical cancer is one of the most common cancers among women, and its recurrence is a serious problem in the treatment and prognosis of the disease. The aim of the study is to develop more effective methods for diagnosing recurrent cervical cancer, which will allow detecting them at an early stage and taking appropriate treatment measures. Material and methods: The object of research was the data of a comprehensive examination and treatment of 87 women with breast cancer who were treated at the clinic of the Samarkand Branch of the Republican Specialized Scientific Practical Medical Center of Oncology and Radiology in the period from 2021 to 2023. Results and discussion: In our study, we conducted a comparative analysis of the diagnostic information content of transvaginal ultrasound, colposcopic (CP) with biopsy, and magneticresonance imaging. A total of 87 patients with suspected recurrent cervical cancer (PCC) were studied. Progression of the disease was observed in 55 patients diagnosed with recurrent cervical cancer. These signs were related to ultrasound signs. In addition, during cytological examination using CP. in 6 (10.9%) cases, we observed an echonegative relapse. A case of local relapse was diagnosed in 16 (29%) patients, while regional relapse was diagnosed in 21 (38.1%) cases. Colposcopic studies of patients with cervical cancer showed that the sensitivity to determine relapse up to 1 sm is 95%, 1-2-2 sm-90.9%, and more than 2 sm-93.2%. The accuracy of colposcopy in determining cervical cancer is up to 1 sm -76%, 1-2 sm -80%, and more than 2 sm 82%. Diagnostic specificity up to 1 sm -60%, 1-2 sm -60%, more than 2 sm-83.3%. In the diagnosis of recurrent cervical cancer after complex and/or combined treatment, the value of colposcopy is significantly higher than ultrasound and MRI, so thesensitivity of colposcopy for relapse up to 1 cm was 95.5±1.2%, specificity 60.2±4.3%, accuracy 76±2.8%. The sensitivity of ultrasound in determining relapse up to 1 cm is 80.0±2.3%, the specificity is 62.5±3.8%, and the accuracy is 84.2±6.6%. For MRI, a measure of sensitivity, specificity, and accuracy 66,7±3,6%, 90,5±2%,3%, 83,35±2,8% accordingly. There was no significant difference in resolution in the diagnosis of recurrent cervical stump using ultrasound and MRI (p>0.05).